PENGEMBANGAN MEDIA PEMBELAJARAN ULAR TANGGA UNTUK MEREMEDIASI SISWA SMP PADA MATERI TATASURYA - Rosa Damayanti; Haratua Tiur S; Syukran Mursyid (Universitas Tanjungpura, 2019)
AbstractThis study aims to develop learning using Ular Tangga Fisika learning media using Ular Tangga Fisika in SMP Negeri 1 Sejangkung and Mts Muhammadiyah Sejangkung, and determine the feasibility level of development using Ular Tangga Fisika as a physics learning media in SMP Negeri 1 Sejangkung and Mts Muhammadiyah Sejangkung. This type of research and development (R&D) with development methods using the Borg & Gall model. Development of learning media for Ular Tangga Fisika with 10 stages: (1) research and initial information gathering, (2) planning, (3) initial product format development, (4) initial trial, (5) initial product revision, (6) field trials, (7) product revisions, (8) field tests, (9) final product revisions, and (10) dissemination and implementation. Determination of the level of media feasibility based on the validation expert test. The percentage achieved by material experts conducted by Untan physics education lecturers at 84.375% can mean that dynamic electrical material is in a very feasible category. The percentage achieved by media experts is 81.25%, which means that the snake ladder physics learning media is in a very feasible category. The percentage achieved by science teachers at SMP Negeri 1 Sejangkung and Mts Muhammadiyah Sejangkung by 96.875% can mean that the media is very feasible. The learning media developed is used for conceptual change of students by using the McNemar test. X2 the price of 9.234 for SMP Negeri 1 Sejangkung and 18.7805 for Mts Muhammadiyah Sejangkung. Keywords: Learning Media, Feasibility